Adjuvant effect of a probiotic fermented milk in the protection against Salmonella enteritidis serovar Typhimurium infection: mechanisms involved - de Moreno, Maria Alejandra (2010)
Probiotics may offer protection against Salmonella enteritidis serovar Typhimurium infection via different mechanisms. The aim of this study is to investigate, using mouse models, the effect of the administration of fermented milk containing the probiotic bacteria L. casei DN-114 001 in the protection against Salmonella enteritidis serovar Typhimurium when this product is administered continuously before and after infection or only post-infection. The adjuvant effect of this probiotic fermented milk (PFM) against S. Typhimurium was also evaluated in newborn mice, whose mothers received the PFM during the suckling period or their offspring after weaning. The results obtained showed that PFM administration after salmonella infection was useful to decrease the severity of the infection. The best effect was obtained with continuous PFM administration. In the newborn mice model, PFM administration to the newborn mice after weaning showed the best effect against the pathogen. PFM administration to the mother during the suckling period was beneficial against this enterophatogen when their offspring did not receive probiotics after weaning. Continuous PFM administration to adult mice (before and after infection) was important to maintain the intestinal barrier and the immune surveillance in optimal conditions to diminish the pathway of entrance of salmonella and the spread of this pathogen to deeper tissues. In the newborn mice model, it was observed that PFM administration to the offspring after weaning or their mother during the suckling period had a protective effect against salmonella infection, however, in the mice from mothers that received PFM during nursing which were fed with PFM after weaning, we found a down regulated immune maturity that was not protective against this infection.